Figurative Language in Album “Purpose” by Justin Bieber - Muhammad Syahril Sidiq; Indri Kustantinah; Ririn Ambarini (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to (1) find out the figurative language in the album